Checklist of the ostracod (Crustacea) fauna of Peter the Great Bay, Sea of Japan - Schornikov, Evgeny I. (Zootaxa, 2006)
Studies of the ostracod fauna of Peter the Great Bay are reviewed. Fragmentary data scattered in 37 publications are summarized, resulting in an annotated checklist of 194 species. The superfamily Terrestricytheroidea Schornikov, 1969 is raised to suborder rank, and Cytherois asamushiensis Ishizaki, 1971 is removed to genus Paracytheroma.